POTENSI PENERIMAAN PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN (PBB P2) DESA BANGKA LELAK KABUPATEN MANGGARAI - Yulita Meilinda Kurnia; Karmila Dwi Lestari Mutia (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
ABSTRACT This research aims to determine the potential revenue from Land and Building Tax in Bangka Lelak Village, Manggarai Regency. The data used in this research is qualitative data with primary data sources and secondary data. The data collection technique in this research is triangulation with data analysis methods using the analytical model used by Miles and Huberman. In this research also illustrating the potential revenue from Land and Building Tax in Bangka Lelak Village, Manggarai Regency is IDR 81,840,912 and a potential loss of Land and Building Tax is IDR 76,093,689 due to inhibiting factors caused by the government and taxpayers. Bangka Lelak Village, Manggarai Regency has a large tax potential when viewed from changes in Development, Community Economy and Land Selling Price. Keywords: Potential, Land and Building Tax.